SHARIA FRAUD MODEL: THE FRAUD IN THE CIRCLE OF FAITH - Abd. Mujib (UPT Penerbitan Universitas Jember)
Agency theory necessitates the importance of superfision to management as a party who has full authority over information. Moreover there is a warning that more than half of the perpetrators of fraud is the management. This also applies to Sharia Financial Institution wich are obliged to adhere to two legal umbrellas at once, namely positive law in Indonesia, especially on the principles of sharia as its main foundation. Ideally, based on the concept of sharia does not open up opportunities the occurence of fraud. However, in the Sharia Financial Institution was the potential that exists, as evidenced by the unfolding of several events that deeply tarnished the sanctity of his face. Starting from there, it emerged that there seemed to be something lacking in the fraud concept we had known, from Adam Smith’s Early Fraud concept, Donald Cressey’s The Fraud Triangle that the most famous concept, to the latest concept The New Fraud Diamond owned by Kranacher et al. From the evolution of the concept of fraud, we feel is still one neglected element, the element of faith, the core of spiritual values. From there we offer the basic concept of Sharia Fraud Model as new thinking to be discussed and examined more deeply.